Pengaruh Lingkungan Kerja Fisik Dan Standar Operasional Prosedur Terhadap Produktivitas Kerja Karyawan Pada PT. BPR Majalengka Jabar - R. Neny Kusumadewi (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2022)
This study aims to determine the effect of the physical work environment and standard operating procedures on the work productivity of employees at PT. BPR Majalengka Jabar partially. The object of this research is PT. BPR Majalengka Jabar. The method used in this study is a survey method using a descriptive analysis approach and verification. The population in this study are employees of PT. BPR Majalengka Jabar with a sample of 55 respondents. The sampling technique used is the saturated sampling technique. The data collection technique is by using a questionnaire. The measurement scale of this study uses a Likert scale. Testing of data instruments is done by testing the validity and reliability. While the data analysis used is the classical assumption test, multiple linear regression analysis, coefficient of determination analysis and model feasibility test. Hypothesis testing in this study uses partial hypothesis testing. The results of respondents' responses indicate that the physical work environment and standard operating procedures are in the good category, while work productivity is in the high category. The results of partial hypothesis testing of this study indicate that the physical work environment has a significant effect on work productivity. Standard operating procedures have a significant effect on work productivity.